Prediction of Phase Equilibrium Conditions and Thermodynamic Stability of CO2-CH4 Gas Hydrate - Ma, Haoran; Liu, Jiaqi; Zhang, Yunyi; Li, Jingming; Kan, Jingyu; Li, Nan (Applied sciences, 2024)
With the large-scale promotion and application of CO2 flooding, more and more engineering problems have emerged. Due to the high CO2 mole fraction, the associated gas of CO2 flooding very easily forms solid hydrates, compared to conventional natural gas. This has resulted in production decline or shutdown. Understanding the phase equilibrium conditions for hydrate formation in production fluids is crucial for hydrate prevention and control. In this study, accurate predictions of CO2-CH4 mixed gas hydrate formation conditions were performed using theoretical models. The temperature and pressure ranges for hydrate formation were calculated for different CO2 mole fraction, ranging from −11.5 °C to 20.85 °C and from 0.81 MPa to −28.1 MPa, respectively. Based on the calculated phase equilibrium data, a multi-parameter empirical model was developed using polynomial fitting. The calculation errors for the multi-parameter empirical model were 3.09%. The multi-parameter empirical model established in this study can avoid complex thermodynamic equilibrium calculations and has the advantages of simplicity, high accuracy, and wide coverage of downhole conditions. Based on the calculated phase equilibrium data, the dissociation enthalpy of CO2-CH4 hydrate below and above the freezing point of water was calculated. The results showed that an increase in CO2 mole fraction led to an increase in hydrate dissociation enthalpy and enhanced thermodynamic stability, making hydrate prevention more challenging. Our work can contribute to the optimization of CO2 production fluid treatment processes and the development of hydrate prevention and control technologies.